Analisa Pengaruh Terhadap Kebijakan Hutang Perusahaan ( Studi Empiris Perusahaan Sub Sektor Otomotif Dan Komponen Yang Terdaftar Di Bursa Efek Indonesia) - Syahdina, Aang; Yan Darmawan; Phebe Octavia Indiarto; Abel Lourensya; Fadel Irza Firmansyah; Salma Andani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Debt policy is crucial in financing decisions that impact company value and shareholder interests. Listed companies in automotive also component manufacturing industries (IDX) 2020 to 2024 will have their debt policies examined at research. Variables which are considered include sales growth, asset composition, and free cash flow. Panel data regression analysis is the quantitative tool used in this investigation. The yearly financial reports of seven businesses chosen for their goals provided further data. Debt management is positively affected by asset structure, significantly negatively affected by sales growth, and unaffected by free cash flow. A 97.83% coefficient of determination indicates that all three factors are significantly influencing the outcome. This study implies organizations experiencing rapid sales growth often have a tendency to lower their debt levels, but the inverse is true for companies with greater asset structures.